Identification of a Bipotent Epithelial Progenitor Population in the Adult Thymus - Ulyanchenko, Svetlana (Cell Rep, 2016)
Thymic epithelial cells (TECs) are critically required for T cell development, but the cellular mechanisms that maintain adult TECs are poorly understood. Here, we show that a previously unidentified subpopulation, EpCam(+)UEA1(−)Ly-51(+)PLET1(+)MHC class II(hi), which comprises <0.5% of adult TECs, contains bipotent TEC progenitors that can efficiently generate both cortical (c) TECs and medullary (m) TECs. No other adult TEC population tested in this study contains this activity. We demonstrate persistence of PLET1(+)Ly-51(+) TEC-derived cells for 9 months in vivo, suggesting the presence of thymic epithelial stem cells. Additionally, we identify cTEC-restricted short-term progenitor activity but fail to detect high efficiency mTEC-restricted progenitors in the adult thymus. Our data provide a phenotypically defined adult thymic epithelial progenitor/stem cell that is able to generate both cTECs and mTECs, opening avenues for improving thymus function in patients.